2015
DOI: 10.1177/1947603515600219
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Collagen versus Synthetic-Based Meniscal Scaffolds in Treating Meniscal Deficiency in Young Active Population

Abstract: Purpose:The aim of this study was to compare the effectiveness of 2 different meniscal scaffolds in treating patients with irreparable partial medial meniscal tear and patients complaining of pain in the medial compartment of the knee due to a previous partial medial meniscectomy. Based on previous studies, we hypothesized that both the scaffolds are effective in improving clinical outcomes in these patient populations.Material and Methods:Twenty-eight patients underwent collagen-based medial meniscus implanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 26 publications
(74 reference statements)
0
72
0
1
Order By: Relevance
“…187,188 Other synthetically derived meniscus scaffolds, such as Actifit R (Orteq Bioengineering Ltd, London, UK), present an alternative to collagen-based scaffolds and have been shown to be just as effective in the short term. 189 Leroy et al 190 recently reported that failure rates for Actifit R remain relatively high after 5-year follow-up. Despite the advancements in enhancing meniscus healing and regeneration using bioresorbable scaffolds, the challenges to control implant resorption and maintain durability persist.…”
Section: Tissue Engineeringmentioning
confidence: 98%
See 1 more Smart Citation
“…187,188 Other synthetically derived meniscus scaffolds, such as Actifit R (Orteq Bioengineering Ltd, London, UK), present an alternative to collagen-based scaffolds and have been shown to be just as effective in the short term. 189 Leroy et al 190 recently reported that failure rates for Actifit R remain relatively high after 5-year follow-up. Despite the advancements in enhancing meniscus healing and regeneration using bioresorbable scaffolds, the challenges to control implant resorption and maintain durability persist.…”
Section: Tissue Engineeringmentioning
confidence: 98%
“…Superior short‐term and long‐term clinical improvements have been reported using absorbable collagen implants for meniscal tears that have undergone partial meniscectomies . Other synthetically derived meniscus scaffolds, such as Actifit ® (Orteq Bioengineering Ltd, London, UK), present an alternative to collagen‐based scaffolds and have been shown to be just as effective in the short term . Leroy et al .…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Clinical studies reported improvement in clinical outcomes scores despite evidence of scaffold resorption and extrusion on MRI,86–89 and two case series reported a 62% survival of implants at 5 year follow-up 87 88. Bulgheroni et al compared subjects with CMI and porous polymer scaffold implants and found clinical improvement in both groups with no statistical difference in outcomes between CMI and polymer scaffolds 90. While studies show improved results with cell-seeded scaffolds compared with injections or cell-free scaffolds, very little research has compared the efficacy of different cell and scaffold compositions with one another 91.…”
Section: Bodymentioning
confidence: 99%
“…Therefore, cell-free strategies may have a broader clinical application. There are two kinds of cell-free meniscal scaffolds currently in clinical use: (1) the collagen meniscus implant (CMI; Ivy Sports Medicine, Montvale, NJ) and (2) the Actifit scaffold (Orteq, London, England) [ 56 ]. Both have been shown to reduce pain and improve knee function when used to treat partial meniscal defects.…”
Section: Cell-free Strategies For Meniscus Repair and Regenerationmentioning
confidence: 99%